(untitled) (Simbiótica. Revista Eletrônica, 2024)
The article aimed to historicize the conceptual meaning of hunger and its methods of combat throughout Brazilian history, emphasizing the significant advances, especially from the 20th century until the beginning of 21th century. Among these advances, the creation of Food Supply Centers, which involve coordination, expertise, distribution, and organization, stands out. Additionally, the importance of raising workers’ incomes, the fundamental role of school meals in providing quality student nutrition, and the connection with local producers were highlighted. The research methods included legal/documentary analysis, indicator analysis, and a review of specific literature. It is concluded that the fight against hunger only became successful with the effective creation of the Public Food Security Policy, which provided a more structured and effective framework to tackle the problem of hunger in the country.